2017
DOI: 10.4172/2157-7471.1000422
|View full text |Cite
|
Sign up to set email alerts
|

Can CRISPR Win the Battle against Huanglongbing?

Abstract: Huanglongbing (HLB) is the most destructive disease of citrus. The causal agent is Candidatus Liberibacter spp. The pathogen is phloem-limited gram-negative bacterium. HLB has caused huge loss in citrus fruit production. All commercial citrus cultivars can be infected by this disease and there is no cure for it. Disease detection, host responses upon infection are under review in this article. Because conventional breeding can't confer citrus resistance to HLB, transgenic approach is an alternative way to prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Therefore, they suggested that this rootstock can allow trees in younger stages to overcome the adverse effects of the disease [34]. The tolerance mechanism of this rootstock against HLB occurs through the expression of proteins not susceptible to diseases (lectin-related proteins, hitinase, and miraculin-like protein), the photosynthesis protein, and redox homeostasis [35].…”
Section: Plant Height and Stem Diametermentioning
confidence: 99%
“…Therefore, they suggested that this rootstock can allow trees in younger stages to overcome the adverse effects of the disease [34]. The tolerance mechanism of this rootstock against HLB occurs through the expression of proteins not susceptible to diseases (lectin-related proteins, hitinase, and miraculin-like protein), the photosynthesis protein, and redox homeostasis [35].…”
Section: Plant Height and Stem Diametermentioning
confidence: 99%